DESKRIPSI KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK SISWA DALAM MENYELESAIKAN MATERI BILANGAN CACAH SAMPAI 1000 - Putri Purwaningrum, Jayanti; Ahyani, Latifah Nur (Universitas Swadaya Gunung Jati., 2024)
This research aims to describe students' numeracy abilities. The subjects of this research were Class IV students at SD N 4 Karangmalang, Kudus Regency. The instruments used in this research were questionnaires, observation sheets, interview guides and numeracy ability tests. The numeracy ability test in this study took the form of story questions covering 10 numbers based on 3 indicators of numeracy ability. The data analysis techniques used are based on Miles and Hiberman, namely data reduction, data presentation, and drawing conclusions. Meanwhile, in order to test the validity of the data, a triangulation method was carried out, namely comparing interview data with test result data. The research results stated that numeracy literacy skills with high initial ability subjects can state 3 indicators, numeracy literacy ability with medium initial ability subjects can state 2 indicators, and numeracy literacy ability with low initial ability subjects can only state 1 indicator. The indicator of numeracy ability consists of 3 indicators, namely being able to use various symbols and numbers related to basic mathematics in order to solve problems in various contexts of real life, carrying out analysis of information presented in various forms (diagrams, charts, tables, graphics, etc.) ), as well as interpreting the results of the research in order to calculate and make decisions